Employees with Autism Spectrum Disorder Achieving Long-Term Employment Success: A Retrospective Review of Employment Retention and Intervention. (September 2018) - Brooke, Valerie; Brooke, Alissa Molinelli; Schall, Carol; Wehman, Paul; McDonough, Jennifer; Thompson, Katherine; Smith, Jan
Policymakers, researchers, and state vocational rehabilitation administrators share an interest in the long-term outcomes of individuals participating in the public state vocational rehabilitation program. Yet, there is limited research in the area of job retention or the service delivery practices used to support individuals with disabilities to achieve long-term success in competitive integrated employment (CIE). This article begins to address this research gap by conducting a retrospective review of 139 records of individuals with autism spectrum disorder (ASD) that were referred to an employment support organization for CIE between October 1, 2009 and December 31, 2017. In comparison to the high national unemployment rate experienced by individuals with ASD, 104 individuals that were referred for CIE secured employment in 126 different jobs. Findings indicate that most study participants were able to move from moderate and intensive levels of support to minimal levels of support by 18 months of employment. It appears that employees with ASD benefit from the continual assessment and subsequent support that occurs during the extended service component of ongoing support services for supported and customized employment. Services that were offered during this phase included ongoing customization of the initial job, lateral job moves, and career advancement.